When is a journalist not a journalist? Negotiating a new form of advocacy journalism within the environmental movement - Phil Vine (Pacific Journalism Review, 2017)
Commentary: A New Zealand broadcast journalist of 25 years’ experience comes under fire from former colleagues after joining the environmental campaigning organisation Greenpeace. The ensuing criticism provides insight into how the mainstream media views itself and how sensitive it might be to any perceived threat to its credibility. It opens up an argument about what constitutes a ‘journalist’ in a contemporary context.  A troubling epoch for journalists facing tight newsroom budgets, news trivialisation, fragmented media spheres and dwindling public confidence in the profession. This commentary examines the argument for new terminology to describe the kind of investigative journalism which might be practised within non-government organisations (NGOs) for a mainly digital audience. It also challenges views on objectivity and bias, positing whether advocacy journalism with strict ethical guidelines produced from within an organisation with a known agenda, may serve the public interest more ably than a fragmented mainstream journalism compromised by less obvious biases.